ATHENA Research Book, Volume 2 (University of Maribor Press, 2023)
The ATHENA European University is an alliance of nine Higher Education Institutions with the mission of fostering excellence in research and innovation by facilitating international cooperation. The ATHENA acronym stands for Advanced Technologies in Higher Education Alliance. The partner institutions are from France, Germany, Greece, Italy, Lithuania, Portugal, and Slovenia: the University of Orléans, the University of Siegen, the Hellenic Mediterranean University, the Niccolò Cusano University, the Vilnius Gediminas Technical University, the Polytechnic Institute of Porto, and the University of Maribor. In 2022, two institutions joined the alliance: Maria Curie-Skłodowska University from Poland and University of Vigo from Spain. Also in 2022, an institution from Austria joined the alliance as an associate member: Carinthia University of Applied Sciences. This research book presents a selection of the ATHENA university partners’ research activities. It incorporates an overview of the research activities of each member, a selection of the most relevant bibliographic works of the members, peer-reviewed student papers, a descriptive list of the ATHENA Talks and reports from the individual work packages of the ATHENA project. The ATHENA Research Book provides a platform that promotes joint and interdisciplinary research projects of both advanced and early-career researchers.